Integrated Serum Pharmacochemistry, Metabolomics, and Network Pharmacology to Reveal the Material Basis and Mechanism of Danggui Shaoyao San in the Treatment of Primary Dysmenorrhea - Xiong, Hui; Li, Na; Zhao, Lanqingqing; Li, Zhe; Yu, Yongzhou; Cui, Xiaoyan; Liu, Qi; Zhao, Chunying (Frontiers in Pharmacology, 2022)
Danggui Shaoyao San (DSS), a well-known formula, has been successfully applied in treating primary dysmenorrhea (PD) in China. However, its material basis and mechanism are still unrevealed. This current research aims to reveal the material basis and mechanism of DSS in treating PD by an integrative approach of serum pharmacochemistry, metabolomics and network pharmacology. The results showed that DSS markedly relieved the physiological and pathological symptoms of PD as confirmed by the improvement of writhing behavior, inhibition of uterine edema, callback of clinical biochemical indexes and metabolic profiles. Furthermore, a metabolomics analysis demonstrated that the therapeutic effect of DSS was attributed to the modulation of arachidonic acid metabolism, pentose and glucuronate interconversions, phenylalanine metabolism. Meanwhile, 23 blood ingredients were identified after the oral administration of DSS. By analyzing the correlation coefficient of the identified biomaker and blood components, active compounds closely associated with core metabolic pathways were extracted. Taken these active compounds as a basis, network pharmacology prediction was executed. It was found that active components of DSS including alisol B,23-acetate, chlorogenic acid, levistilide A, cianidanol, senkyunolide A, atractylenolide II, and sedanolide, were germane to steroid hormone biosynthesis, arachidonic acid metabolism, sphingolipid signaling pathway, etc. Interestingly, PTGS2 and PTGS1 related to arachidonic acid metabolism may be pivotal targets of DSS. The current study proved that the integration of serum pharmacochemistry, metabolomics and network pharmacology, was a powerful approach to investigate the material basis and the molecular mechanisms of DSS, and provided a solid basis for DSS application.